18F-PSMA-1007 PET/CT-derived semi-quantitative parameters for risk stratification of newly diagnosed prostate cancer - Dong, Siying; Li, Yanmei; Chen, Jian; Li, Yongliang; Yang, Pengfei; Li, Juan (Frontiers in Oncology, 2022)
Abstract Purpose: This study aimed to assess the value of 18F-PSMA-1007 positron emission tomography/computed tomography (PET/CT)-derived semi-quantitative parameters for risk stratification of primary prostate cancer (PCa). Methods: Sixty patients referred for 18F-PSMA-1007 PET/CT imaging for primary PCa were retrospectively analyzed and classified into the low-intermediate-risk (LIR) or high-risk (HR) group. The maximum standardized uptake value (SUVmax), prostate total lesion PSMA (TL-PSMAp), and prostate PSMA˗tumor volume (PSMA-TVp) were measured, and group differences were evaluated using the Mann–Whitney U test. Spearman’s correlation was performed to assess the correlation between the above parameters with prostate-specific antigen (PSA) levels and Gleason score (GS). Receiver operating characteristic (ROC) curve analysis was used to determine optimal cut-off values for SUVmax, TL-PSMAp, and PSMA-TVp to identify high-risk PCa and compare diagnostic efficacy. Results: Among 60 patients, 46 were assigned to the HR group and 16 to the LIR group. In all patients, SUVmax, TL-PSMAp, and PSMA-TVp were moderately correlated with pre-treatment PSA values (r = 0.411, p = 0.001; r = 0.663, p < 0.001; and r = 0.549, p < 0.001, respectively). SUVmax and TL-PSMAp were moderately correlated with GS (r = 0.457 and r = 0.448, respectively; p < 0.001), while PSMA-TVp was weakly correlated with GS (r = 0.285, p = 0.027). In the ROC curve analysis, the optimal cut-off values of SUVmax, TL-PSMAp, and PSMA-TVp for identifying high-risk PCa were 9.61, 59.62, and 10.27, respectively, and the areas under the operating curve were 0.828, 0.901, and 0.809, respectively. The sensitivities of SUVmax, TL-PSMAp, and PSMA-TVp were 91.03%, 71.74%, and 63.04%, respectively, and the specificities were 71.43%, 100.00%, and 92.86%, respectively. Conclusions: TL-PSMAp had a superior ability to identify high-risk PCa. The semi-quantitative parameters derived from 18F-PSMA-1007 PET/CT can be an objective imaging reference index to determine PCa risk stratification.